Rola honoru w Sadze o Egilu - Barreiro, Santiago (Średniowiecze Polskie i Powszechne, 2016)
This article examines the role played by honor in the 13th-century Icelandic Saga of Egil (composed roughly between 1220 and 1240). The theoretical and historiographical records of the concept of honor are analyzed in a general sense and in the context of the Icelandic Middle Ages. In addition, the author explores the honor-related vocabulary occurring in the saga to distinguish, based on it, its heroes who could serve as examples of honor. In turn, the last part of the article engages in a dialogue with the concept of honor conceived as a commodity and proposes an alternative reading of its meaning. In this view, honor is likened to inalienable wealth, and the author proves his hypothesis with a brief analysis of one of the saga's scenes.